Statistical Modeling of the Ecological Risks as a Factor of the Ecological Safety - Cherenkevych, O. S. (Statistics of Ukraine, 2020)
In modern conditions, the priority of Ukraine’s national interests is to ensure environmentally safe living conditions of society, as well as the preservation and restoration of the natural environment, increasing requirements for environmental safety. The purpose of this article is the statistical modelling of environmental risks to determine the direction of justification of management decisions on environmental safety. This necessitates the implementation of the effective methods of environmental safety regulation, assessment and monitoring of environmental risk. The author clarifies the definition of environmental safety as a set of conditions and processes that provide all vital human needs and do not provide for the deterioration of the future generations living conditions in terms of economic and environmental balance to achieve sustainable economic development. As an object of statistical research, environmental safety is a component of national security, which reflects the quantitative parameters of the environmental pollution risks. The environmental risks’ modelling is performed by using trend models in the article. The difference between the real levels of air and water resources pollution, as well as the generation of hazardous waste of I-III classes and their theoretical values calculated by the model, assesses the pollution risk of the corresponding environmental resource. The specific cost of air pollution, water bodies, and hazardous waste is defined as the ratio of the amount of environmental payments of the last year to the amount of actual pollution of the same year, that is environmental payments per 1 unit of pollution. Further assessment of the risk cost is proposed to be defined as the product of the calculated deviations excess proportion and the specific cost of pollution by types. For Ukraine today the most acute problems are pollution of water resources, as well as the formation of hazardous waste, much lower than air pollution. The obtained results allow drawing a conclusion about the inefficiency of the current payment system for environmental pollution and compensation for damage, which requires an increase in capital investment in environmental equipment, increasing fines for non-compliance with pollution standards.